Potensi Mikroenkapsulasi Ekstrak Daun Stevia Rebaudiana Terhadap Kadar Trigliserida Tikus Putih Jantan Galur Wistar Hiperlipidemia - Mutmainah Mutmainah; I Kadek Bagiana; Ika Puspitaningrum; Lia Kusmita; Yani Kresnawati (Journal of Pharmaceutical and Health Research, 2023)
Coronary heart disease is a cardiovascular disease caused by atherosclerosis. Hyperlipidemia is known as a risk factor for atherosclerosis. The Stevia rebaudiana Bertoni plant is a plant that is efficacious as a hypolipidemic. This study aims to determine the effect of microencapsulated preparations of Stevia rebaudiana Bertoni leaf extract on triglyceride levels in male Wistar rats. One way to improve the formulation is by using the encapsulation process. The encapsulants used are inulin and chitosan. This research was conducted with the aim of making hyperlipidemic rats induced by alloxan at a dose of 150 mg/KgBW rats intraperitoneally. Hyperlipidemic rats were given microencapsulated Stevia rebaudiana Bertoni leaf extract at different dose levels (100, 300, 700, and 1000 mg/kg BW) for 8 weeks; control mice were fed a basal diet during this period. The results of the study concluded that microencapsulation of Stevia rebaudiana Bertoni leaf extract had the potential to reduce triglyceride levels in hyperlipidemic male Wistar rats.